Calculations, Phonse Ducey's twine store, Keels, NL - Whitney, Erin (2012)
Writing on wall of Phonse Ducey's twine store in Keels, NL. Appears to be a calculation determining how many “meshes” (ready made nets?) would be required to reach 18 fathoms.